Conflict, interdependence, and justice the intellectual legacy of Morton Deutsch - Coleman, Peter T. (Springer eBooks., 2011)
Morton Deutsch is considered the founder of modern conflict resolution theory and practice. He has written and researched areas which pioneered current efforts in conflict resolution and diplomacy. This volume showcases six of Deutsch's more notable and influential papers, and include complementary chapters written by other significant contributors working in these areas who can situate the original papers in the context of the existing state of scholarship.